2021
DOI: 10.1099/mgen.0.000684
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics and population genomics of SARS-CoV-2 in Mexico during the pre-vaccination stage reveals variants of interest B.1.1.28.4 and B.1.1.222 or B.1.1.519 and the nucleocapsid mutation S194L associated with symptoms

Abstract: Understanding the evolution of the SARS-CoV-2 virus in various regions of the world during the Covid-19 pandemic is essential to help mitigate the effects of this devastating disease. We describe the phylogenomic and population genetic patterns of the virus in Mexico during the pre-vaccination stage, including asymptomatic carriers. A real-time quantitative PCR screening and phylogenomic reconstructions directed at sequence/structure analysis of the spike glycoprotein revealed mutation of concern E484K in geno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 70 publications
(94 reference statements)
0
12
0
Order By: Relevance
“…5 ). Recent studies revealed an association of strains having this substitution and symptomatic patients ( Barona-Gomez et al, 2021 ). Another recent study revealed that one of the most important B and T cell epitope of the N protein lies between residues 305–340 ( Ahmed et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…5 ). Recent studies revealed an association of strains having this substitution and symptomatic patients ( Barona-Gomez et al, 2021 ). Another recent study revealed that one of the most important B and T cell epitope of the N protein lies between residues 305–340 ( Ahmed et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in the NSP12 region that are involved in RNA-dependent RNA polymerase (RdRp) expression have been shown to contribute toward 5.9 times increased disease severity ( Voss et al., 2020 ). Additionally, the mutation S194L in N protein was reported to be associated with the symptomatic patients and is located in the flexible linker region of the protein N ( Zeng et al., 2020 ; Barona-Gómez et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The non-synonymous mutations identified in Chaetophractus villosus have not been reported previously in other animals infected naturally or experimentally with SARS-CoV-2 Gamma variant. A change in N 194 has been described in human sequences as N_S194L (with a potential association with symptomatic patients (18) but in experimental infections in cats, dogs and mice the change is different (N_S194T) (19). There are no records of ORF6_ I14T and NSP12_ R905K changes in SARS-CoV-2 infected animals.…”
Section: Discussionmentioning
confidence: 99%